Embedding Secure Coding Instruction Into the IDE: Complementing Early and Intermediate CS Courses With ESIDE. (June 2018) - Whitney, Michael; Lipford, Heather Richter; Chu, Bill; Thomas, Tyler
Many of the software security vulnerabilities that people face today can be remediated through secure coding practices. A critical step toward the practice of secure coding is ensuring that our computing students are educated on these practices. We argue that secure coding education needs to be included across a computing curriculum. We are examining an approach that complements traditional classroom instruction by turning the student's integrated development environment into an educational resource for secure coding instruction. In this article, we report on two formative and one summative study using our tool Educational Security in the Integrated Development Environment (ESIDE) in early and intermediate computer science programming courses. Our results support the viability of this approach to increase secure programming knowledge and awareness of students and also to identify several challenges for maximizing the learning opportunities within programming courses.